SOSIALISASI TATA CARA PENYELENGGARAAN SIDANG PERKARA PIDANA PADA TINGKAT PENGADILAN NEGERI - Firmansyah, Hery; Putra, Surya Dharma; Siahaan, Shinta Aulia; Michelle, Grace Bernadette; Gunawan, Angelene Vivian; Cendranita, Ivannia (Jurnal Serina Abdimas, 2024)
This research aims to socialize the procedures for holding criminal case trials at the District Court level to inmates. Community Service (PKM) at the Salemba Detention Center was carried out offline with the one-way presentation of material involving lawyers and students from PKBH Untar. The Criminal Procedure Code has explained the stages in a criminal case trial from the first instance, appeal, cassation, and judicial review to the implementation of the judge's decision. The research results show that this outreach is effective in increasing legal awareness and understanding of the trial process among inmates. Through this PKM, it is hoped that they can reduce their uncertainty and anxiety, as well as encourage active and cooperative involvement in the legal process. ABSTRAK Penelitian ini bertujuan untuk mensosialisasikan tata cara penyelenggaraan sidang perkara pidana di tingkat Pengadilan Negeri kepada para warga binaan. Pengabdian Kepada Masyarakat (PKM) di Rutan Salemba dilakukan secara luring dengan pemaparan materi searah yang melibatkan pengacara dan mahasiswa dari PKBH Untar. KUHAP telah menjelaskan tahapan - tahapan dalam sidang perkara pidana dari tingkat pertama, banding, kasasi, dan peninjauan kembali hingga pelaksanaan putusan hakim. Hasil penelitian menunjukkan bahwa sosialisasi ini efektif dalam meningkatkan kesadaran hukum dan pemahaman tentang proses persidangan di antara warga binaan. Melalui PKM ini, diharapkan dapat mengurangi ketidakpastian dan kecemasan mereka, serta mendorong keterlibatan aktif dan kooperatif dalam proses hukum.